"Niños de las guarderias Louise Michel, con los miembros de la CNT en el acto de inauguracion". Sanz and Pauli next to each other right of the centre. Esgleas left of the centre. Series of 2 photos. Copied from CNT collection
"Niños de las guarderias Louise Michel, con los miembros de la CNT en el acto de inauguracion". Sanz and Pauli next to each other right of the centre. Esgleas left of the centre. Series of 2 photos. Copied from CNT collection.